Modelul slavon versus modelul latin în textele biblice româneşti - Eugen Pavel (Revista de Istorie și Teorie Literară)
In the beginning, there are examined several perspectives on the authority of the Slavonic originals in the compilation of the first Romanian translations of the biblical text in the sixteenth century, against the background of their rather pale contenders, namely the Latin model and, respectively, the German one. The hypothesis that the primitive translation of the Psalms into Romanian valorized a previous translation from Latin – possibly from the Psalterium Romanum, a translation that was supposedly revised or rewritten on the basis of a Slavonic version, for inclusion in the Oriental canon – is not sufficiently credible. Nor is the opinion concerning the use of Luther’s original in the translation of portions of text from the Tetraevangelion of Sibiu in 1551–1553 irrefutable, as in these passages there are also similarities with Theodore Beza’s edition of the New Testament. The actual mutation from the Slavonic to the Latin model occurred only at the middle of the eighteenth century, with the printed versions that appeared in Alba Iulia, which adopted the sources of Greek-Latin humanism, consecrated in the European space through the new translations of the biblical text made by Sante Pagnini and Theodore Beza. The complete editions of Holy Scripture into the Romanian language, among which were included the 1688 Bible from Bucharest and the 1795 Bible from Blaj, were largely derived from the Greek model, more specifically, from the Septuagint, while the Slavonic and Latin sources were relegated to the background, without being totally ignored. The Latin model categorically imposed itself through the translation of the Vulgate into Romanian, in 1760–1761, by the Transylvanian Bishop Petru Pavel Aron and his collaborators, whose source was a revised version, published in Rome in 1592 and re-edited in 1593 and 1598: the so-called Bible of Pope Clement VIII (Sixto-Clementina).